2021
DOI: 10.1080/12298093.2021.1938803
|View full text |Cite
|
Sign up to set email alerts
|

Two Arbuscular Mycorrhizal Fungi Alleviates Drought Stress and Improves Plant Growth in Cinnamomum migao Seedlings

Abstract: Cinnamomum migao plants often face different degrees of drought in karst habitats, which can lead to plants' death, especially in the seedling stage. Widespread of arbuscular mycorrhizal (AM) fungi in karst soils have the potential to address this drought, which is a threat to C. migao seedlings. We inoculated C. migao seedlings with spores from Glomus lamellosum and Glomus etunicatum, two AM fungi widely distributed in karst soils, to observe seedling growth response after simulated drought. Our results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The bark and wood of C. migao can be used as raw materials for making paper and wood slab. The fruit of C. migao contains a large amount of volatile oil and monoterpene or sesquiterpene chemicals; it is a traditional medicinal material of the Miao people in China and is used to cure gastrointestinal and cerebrovascular diseases (Huang et al, 2019; Liao et al, 2021). However, researchers discovered that the allelopathic and autotoxic nature of C. migao kept its population size small and range of species distribution narrow.…”
Section: Introductionmentioning
confidence: 99%
“…The bark and wood of C. migao can be used as raw materials for making paper and wood slab. The fruit of C. migao contains a large amount of volatile oil and monoterpene or sesquiterpene chemicals; it is a traditional medicinal material of the Miao people in China and is used to cure gastrointestinal and cerebrovascular diseases (Huang et al, 2019; Liao et al, 2021). However, researchers discovered that the allelopathic and autotoxic nature of C. migao kept its population size small and range of species distribution narrow.…”
Section: Introductionmentioning
confidence: 99%
“…should be considered. Their activity in the reduction of stress effects has been proven in lettuce ( Ruiz-Lozano et al, 1995b ), Lavendula spica ( Marulanda et al, 2007 ), and Cinnamonum migao ( Liao et al, 2021 ). Another natural solution for the improvement of plant tolerance to unfavorable conditions is inoculation with different strains of Bacillus sp., as revealed in Capsicum annuum ( Lim and Kim, 2013 ), Z. mays ( Moreno-Galván et al, 2020 ), Solanum lycopersicum ( Gowtham et al, 2020 ), Glycine max ( Sheteiwy et al, 2021 ), Cenchrus americanus ( Kushwaha et al, 2020 ), and Helianthus annus ( Sandhya et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…reduces the content of proline under drought; however, its level was higher than in control ( Figure 2 ). Liao et al (2021) suggested that Glomus improves the growth of Cinnamonum migao through better absorption of nutrients and water uptake, ensuring a high turgor of tissues, and thus it is not necessary to synthesize large amounts of osmoprotectants. However, different Bacillus strains increased proline secretion in drought conditions in Solanum lycopersicum ( Shintu and Jayaram, 2015 ), Cicer arietinum ( Sharma et al, 2013 ), Sorghum bicolor ( Grover et al, 2014 ), and Cucumis sativus ( Wang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2006) Glomus mosesseae Fragaria x ananassa Yin et al. (2010) Glomus lamellosum Cinnamomum migao Liao et al. (2021) Glomus mosseae Poncirus trifoliata Wu et al.…”
Section: Biotechnological Applications Of Drought Adaptive-microbesmentioning
confidence: 99%